Studies on the immature stages of the planthopper Lepidelphax pistiae (Hemiptera: Delphacidae), a potential biocontrol agent for the aquatic weed Pistia stratiotes (Araceae) from Argentina - Marino de Remes Lenicov, Ana María (2017)
Descriptions of the immature stages of the planthopper Lepidelphax pistiae Remes Lenicov (Delphacidae), a specialist herbivore of Pistia stratiotes L.(Alismatales: Araceae) from Argentina, are provided. Newly emerged nymphs from eggs collected in the field, were reared in rearing chambers. Fifth nymphal instars may be easily recognized by the whitish coloration with a distinctive blackish antennal flagellum and ungues, and the relatively long frons and rostrum. Information is provided on nymphal behavior and the main features of the fifth nymph instar that distinguishes it from the two other delphacids that live and feed on plants from centraland northern Argentine wetlands.